Liquidity premium in global corporate bonds. - Hu, Enwei. (2011)
This paper examines the effect of liquidity shocks on the pricing of corporate bonds from a global perspective. We study the exposure of global corporate bond returns to the equities markets and sovereign liquidity risk over the period of 1999 to 2009. We discover that there is negative relationship between illiquidity and pricing of corporate bonds, which is consistent with findings from other papers. Liquidity risk is especially significant during times of crisis in Speculative Grade bonds compare to Investment grade bonds. For G7 versus non G7 countries, our research shows that liquidity shocks were highly significant in the G7 countries. G7 nations were more affected during the 2008 Sub-prime Mortgage Crisis. These documented effects are robust to controlling for other systematic risk such as term structure and default factor. Overall, the model is able to conclude that liquidity risk premium is priced globally. Our findings are also consistent with the concept of “flight-to-liquidity” and “flight-to-quality”.